High Risk Human Papilloma Virus Genotype Distribution in Cervical Intraepithelial and Invasive Carcinoma - Aliya Zaman; Nazish Jaffar; Shahnaz Imdad Kehar; Rubina Ghani; Jawed Iqbal; Marvi Umair (ziauddin University, 2020)
Background: High-risk (HR) Human Papillomavirus (HPV) is an established cause of cervical cancer. HPV genotype detection is significant in preventing cervical cancers through targeted vaccination. Our study aimed to identify HRHPV16/18 and non 16/18 in cervical intraepithelial neoplasia (CIN) and squamous cell carcinoma (SCC). Methods: A retrospective study was performed at Pathology Department, BMSI, JPMC, Karachi. About 96 cases of CIN and SCC were included. Analysis of HPV genotypes was performed by DNA extraction, PCR amplification and flow-through hybridization technique. The probes used had a cluster of 13 HRHPV into a group of 3 as HPV HR 1, 2 and 3. Chi square/ Fischer Exact test were applied to observe the association of morphological types of the lesion and expression of HPV genotypes. Results: HPV DNA positivity was 44% in our series. HPV HR 1 was observed in majority of cases (61.9%), followed by HPV 16 in 23.8%, HPV HR 3 in 9.5%, and HPV HR 2 in 4.7% cases respectively. The unique finding was absence of HPV 18 in the series. High grade lesions and invasive cancers showed positivity for HPV HR 1 and HPV 16, while low grade lesions were positive for HPV HR 1, 2 and 3 respectively. Conclusion: HPV HR1 are major causative agents for low and high grade intraepithelial and invasive SCC, followed by HPV 16. Absence of HPV 18 was the novel finding. Our results differ from studies within and outside the region, suggestive of diversified genetic makeup and impact of detection techniques on results.